Transformation Of Religious Moderation Learning At Islamic Boarding School - Mukaffan Mukaffan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This article aims to describe the internalisation of the values of constancy (istiqomah) to strengthen the religious moderation of Raudhatul Ulum Rowokangkung students. This research utilises a qualitative approach to investigate aspects of the natural environment and attempts to interpret these phenomena. Data collection techniques employed observation, interviews, and documentation studies. In this research, researchers used several stages of data analysis, namely the condensation stage, data presentation stage, making temporary conclusions, and verification activities. The research results concluded that the Raudhatul Ulum Rowokangkung Islamic Boarding School internalises the value of religious moderation based on the learning process carried out in four forms: firstly determining competency in achieving moderate learning with Sunni ideology, b) choosing an inclusive learning model, c) through extracurricular activities and d) through habituation activities in worship activities. The four forms of internalising the value of religious moderation in strengthening the moderation attitude of students at the Raudhatul Ulum Rowokangkung Islamic Boarding School, which contains the concepts of faith, Islam, and Ihsan, which are then manifested in learning about religious moderation